2016
DOI: 10.1063/1.4952388
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption of hydrogen-related defects in ammonothermal GaN

Abstract: Polarization controlled Fourier transform infrared (FTIR) absorption measurements were performed on a high quality m-plane ammonothermal GaN crystal grown using basic chemistry. The polarization dependence of characteristic absorption peaks of hydrogen-related defects at 3000–3500 cm−1 was used to identify and determine the bond orientation of hydrogenated defect complexes in the GaN lattice. Majority of hydrogen was found to be bonded in gallium vacancy complexes decorated with one to three hydrogen atoms (VG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 25 publications
3
59
0
Order By: Relevance
“…[43,44,79] The observed vacancy concentration is several orders of magnitude higher than what has been reported for HVPE grown material [78,80] and is expected to have a significant effect on the material properties. In GaN, gallium vacancies (V Ga ) and vacancy complexes form deep levels in the band-gap, [44,81,82] cause non-radiative recombination, [83] contribute to sub-bandgap optical absorption, [42] compensate n-type doping, [40] and have been associated with device degradation.…”
Section: Gallium Vacancies and Vacancy Clustersmentioning
confidence: 60%
See 4 more Smart Citations
“…[43,44,79] The observed vacancy concentration is several orders of magnitude higher than what has been reported for HVPE grown material [78,80] and is expected to have a significant effect on the material properties. In GaN, gallium vacancies (V Ga ) and vacancy complexes form deep levels in the band-gap, [44,81,82] cause non-radiative recombination, [83] contribute to sub-bandgap optical absorption, [42] compensate n-type doping, [40] and have been associated with device degradation.…”
Section: Gallium Vacancies and Vacancy Clustersmentioning
confidence: 60%
“…[26,[34][35][36] Ammonothermal GaN substrates have been used in homoepitaxy [35,37,38] and as substrates for InGaN LDs. [39] Although the crystalline quality of ammonothermal GaN is very high, recent studies have shown that the high concentration of impurities [22,40,41] and native point defects [42][43][44] in the as-grown material have a significant effect on the material properties. The most dominant impurities, oxygen and transition metals, cause absorption in the visible region [23,42] and their non-uniform incorporation in the growing crystal can cause build-up of strain.…”
Section: Progress Reportmentioning
confidence: 99%
See 3 more Smart Citations